Application of solar energy in Malaysia / Ahmad Kazwini Abd Wahab - Ahmad Kazwini, Abd Wahab (2011)
Currently, countries continue to seek the best alternative energy sources for routine uses. Solar energy has continuously attracted attention since it is an available source of energy which does not require any extraction cost. In this study, the solar systems with inverter are analyzed technically through TRNSYS simulation and the economic analysis has also been made. Energy produced from this solar system will significantly cater to the need of energy consumption in the daily life of Malaysians. The data for solar energy was collected from Malaysia metrology department and software (Meteonorm as well as online GAISMA) was analyzed and used in TRNSYS. Two types of solar photovoltaic (PV) panels including Monocrystalline PV and Thin Film PV have been simulated in TRNSYS. At the same time, comparisons of both types of PV are also made for some selected regions in Malaysia such as Kota Bharu, Kelantan, George Town, Pulau Pinang and Petaling Jaya, Kuala Lumpur. Then, the energy outputs of the TRNSYS simulation were analyzed economically. Life Cycle Cost, LCC method has also been implemented in this economic analysis. The analysis will take into account the full cost of materials, operations, inflation rate, etc. to show the flow of future implementation. Using the results of energy output from raw data analysis, TRNSYS simulation, and LCC analysis on the economics of the solar system, this study will provide useful information for finding the sources of renewable energy and their implementation in meeting the demands of domestic consumers.